The Role of the Criminal Investigation Unit in Handling Online Fraud Crimes in the Jurisdiction of the Mojokerto District Police (Indonesian Journal of Police Studies, 2024)
The final project entitled "The Role of the Criminal Investigation Unit in Handling Online Fraud Crimes in the Jurisdiction of the Mojokerto District Police" aims to describe the overview of online fraud crimes and the role of the criminal investigation unit as well as the influencing factors. This research is motivated by the phenomenon of a significant increase in online fraud cases within the jurisdiction of the Mojokerto District Police and adopts a qualitative approach to address the research problems: what is the overview of online fraud crimes in the jurisdiction of the Mojokerto District Police?, what is the role of the criminal investigation unit of the Mojokerto District Police in handling online fraud crimes?, and what are the factors influencing the role of the criminal investigation unit of the Mojokerto District Police in handling online fraud crimes?. This research is a field research utilizing role theory, SWOT theory, as well as the concepts of criminal investigation units and online fraud crimes to address the existing problems. The data sources consist of primary data and secondary data. Primary data include interviews with informants and observations covering investigation and prosecution activities, organizational structure of the unit, and existing facilities or infrastructure at the Mojokerto District Police. The secondary data of this research include documents related to legislation. The findings reveal that online fraud crimes have been one of the relatively high-intensity crimes over the past 3 years within the jurisdiction of the Mojokerto District Police. The Criminal Investigation Unit of the Mojokerto District Police has been fulfilling its role from investigation to prosecution, although in practice, there are still very few online fraud cases classified as P21. Additionally, there are internal and external factors influencing this criminal investigation unit. Internal factors include strengths and weaknesses, while external factors consist of opportunities and threats.
Keywords: Penipuan Online